Desarrollo de una aplicación web y móvil para potenciar el aprendizaje lógico matemático en niños de 2 a 3 años del centro infantil Luceritos del sur de la ciudad de Quito - Cevallos Moya, Brayan Enrique (2022)
This technological proposal was made in the province of Pichincha, city of Quito, to which the problem of the absence of technological resources for the teaching process is identified, in addition, the records of activities in the Luceritos del Sur children's center are made manually, for this reason the objective, is to develop a web and mobile application, to improve the educational process in children, and a better management of activity records, this using freely accessible programming tools such as: Python, JavaScript, PostgreSQL, Android Studio, etc. For the technological proposal, the mixed research methodology was used, applying the design of the research and using techniques for the collection of information, such as: observation, interview, to identify the different requirements. For web development, SCRUM was applied, an agile model based on iterations and continuous revisions, being very effective in the development, for the mobile application, the Mobile-D methodology was used, thus, through the correct monitoring of its phases, the result was the systematization of some educational processes and the proper recording of activities. As a result of this technological proposal, improvements were obtained in the teaching of children and the management of activities, which were analyzed by means of a comparison in the registration times that were used both manually and with the application, finally with the implementation of the software, educators will be able to improve the teaching processes and properly manage the registration of activities, thus satisfying the initial needs and improving the educational process in the nursery.